(untitled) (Italian Journal of Public Health, 2007)
Objective: The aim of the present study is to evaluate the presence of Salmonella spp. and Listeria monocytogenes in ready-to-eat foods by comparing the performance and sensitivity of BIO-RAD commercial Kits based on real-time PCR detection with traditional culture (ISO) procedures. Materials and methods: Sixty-five samples of ready-to-eat foods were analysed as described above. In order to verify the validity of both culture and biomolecolar methods and to compare the sensitivity of real-time PCR versus conventional culture (ISO) procedures, five food samples were artificially contaminated with the Salmonella enteritidis ATCC strain by using scalar concentration from 103 to 10-1 cfu/g while one food sample was artificially contaminated with the Listeria monocytogenes ATCC strain. Finally, statistical analyses of the results were performed using the statistics “K” to confirm the agreement between the compared methods. Results: Both procedures showed the absence of Salmonella spp. and Listeria monocytogenes in the processed samples; results in agreement appeared both for the five food samples artificially contaminated with Salmonella enteritidis ATCC strain and for the food sample artificially contaminated with Listeria monocytogenes ATCC strain. The sensitivity of the biomolecolar test was 1 cfu/g. Therefore full agreement between the two methods was detected, with a K value of 1. Conclusions: The real-time PCR system appears to be extremely useful in the rapid screening of food samples, allowing for the rapid identification of Salmonella spp. and L. monocytogenes.